Parents' perceptions of functional electrical stimulation as an upper limb intervention for young children with hemiparesis: qualitative interviews with mothers - Emma Swaffield; Jaynie F. Yang; Patricia Manns; Katherine Chan; Kristin E. Musselman (BMC, 2022)
Abstract Background/objective To explore parents' perceptions of an upper extremity (UE) intervention using functional electrical stimulation (FES) for young children with hemiparesis. Methods Parents of children aged 3-6 years with a history of perinatal stroke, impaired UE function, and participation in a 12-week FES intervention delivered at a hospital were included in this exploratory qualitative study. Nine mothers participated in a semi-structured interview < 1 week after their child completed the FES intervention (MyndMove®, MyndTec Inc.) targeting the hemiparetic UE. Open-ended questions queried parents' goals, perceived benefits, and challenges of the FES intervention. Interviews were audio recorded and transcribed verbatim. Qualitative conventional content analysis was used to analyze the transcripts. Results Five themes were identified. 1) Parents' expectations for the FES intervention. Mothers described setting functional, exploratory, and realistic goals, yet feeling initial apprehension towards FES. 2) Perceived improvement. Physical, functional, and psychological improvements were observed with FES; however, there was still room for improvement. 3) Factors influencing the FES intervention. Program structure, therapist factors, and child factors influenced perceived success. 4) Lack of access to intensive therapy. Mothers noted that FES is not provided in mainstream therapy; however, they wanted access to FES outside of the study. They also highlighted socioeconomic challenges to accessing FES. 5) Strategies to facilitate participation. The mothers provided suggestions for program structure and delivery, and session delivery. Conclusions Mothers perceived the FES intervention to have physical, functional and psychological benefits for their children. Interest in continuing with FES highlights a need to improve access to this therapy for young children.